Residential High-Speed Internet Among Those Likely to Benefit From an Online Health Insurance Marketplace - Michel H. Boudreaux PhD; Gilbert Gonzales PhD; Lynn Blewett PhD; Brett Fried MS; Pinar Karaca-Mandic PhD (SAGE Publishing, 2016)
Using data from the 2013 American Community Survey, we found that 24.3 million people (about 1 in 4) who were either eligible for Medicaid/Children's Health Inusrance Program (CHIP) or appeared likely to shop for Qualified Health Plan (QHP) lacked residential high-speed Internet. Specifically, 28.6% or 18.9 million people eligible for Medicaid/CHIP and 17.1% or 5.5 million people who appeared likely to shop for a QHP did not have high-speed Internet in the home. For both the Medicaid/CHIP eligible and those likely to shop for a QHP, the proportion of people living in households without Internet varied substantially by race, geography, and other socio-demographic characteristics.